2022
DOI: 10.1007/s10792-022-02216-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corneal density and thickness on tonometry measurement with goldmann applanation, non-contact and iCare tonometry methods

Abstract: Purpose To evaluate the effect of corneal density and thickness on the accuracy of tonometry readings obtained via three most used techniques. Method Intraocular pressures of 45 patients’ right eyes were measured using Goldmann Applanation, iCare, and non-contact tonometry methods. Corneal parameters were obtained using the Pentacam Camera System. Data obtained were analyzed using Paired t Test, Pearson’s correlation coefficient, multiple linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…15 The Goldmann Applanation tonometer (GAT) is less vulnerable to CCT than the NCT. [15][16][17][18][19] NCT causes the cornea to flatten in a brief amount of time-roughly 8 ms-making the cornea more rigid than GAT, which measures the response of cornea to steady pressure or compression. Increased measured IOP with increased CCT are consistent across clinical and demographic research alike.…”
Section: Discussionmentioning
confidence: 99%
“…15 The Goldmann Applanation tonometer (GAT) is less vulnerable to CCT than the NCT. [15][16][17][18][19] NCT causes the cornea to flatten in a brief amount of time-roughly 8 ms-making the cornea more rigid than GAT, which measures the response of cornea to steady pressure or compression. Increased measured IOP with increased CCT are consistent across clinical and demographic research alike.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring CCT is an important parameter in determining IOP by GAT. 12,14 An elevated IOP after PPV can be due to numerous causes including change in CCT. 15 A quickly triggered, inflammatory (TNF-α mediated), IOP-independent process occurring due to acute injury or surgical procedure is also identified.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 This can cause errors in readings of IOP and may lead to false diagnosis of secondaryglaucoma. 11,12 Doughty and Zaman reported that a 10% change in CCT may cause 3.4mmHg change in IOP. 13 This research was designed to assess the outcome of PPV in terms of CCT and its influence on IOP.…”
Section: Introductionmentioning
confidence: 99%